Effect of cactus pear (Opuntia ficus‐indica (L.) Miller) on the antioxidant capacity of donkey milk. (18th December 2017) - Valentini, Valeria; Allegra, Alessio; Adduci, Francesco; Labella, Cristiana; Paolino, Rosanna; Cosentino, Carlo
Abstract : The cladodes of Opuntia ficus‐indica (L.) Miller were fed to lactating donkeys as an alternative food, in order to evaluate effects on the chemical composition and antioxidant activity of their milk. Lactating donkeys were divided into two groups: standard feeding and alternative feeding. With regard to chemical composition, no differences were observed. Total antioxidant capacity was constant in the standard feeding group, while it increased in the alternative feeding group: the radical scavenging activity increased from 95.53% to 96.62% in the ABTS test and from 28.40% to 33.33% in the DPPH test. This indicated that alternative feeding affects the antioxidant capacity of milk.